Hear me : Assistive technology for the deaf and hearing impaired - Diyana, Kamarudin; Elmokri, Razman; Yasmin, Hussain; Hu, Xiaojie; Rahman, Md Mustafizur (2021)
Hearing impairment is one of the topics within special education. This disability is one of the factors contributing to the diffulty of learning in school, which could result in these students being left behind, which could also lead to societal problems later on. Understanding the hand signals or codes is extremely important as this is the main way of communication in class. Not understanding of the sign language could lead to problems for the students as all the teachings would be conducted in sign language. Studies have also shown that deaf children who were not provided with sign language early on in their development are at risk for linguistic deprivation. To the hearing impaired, sign language is one way of communicating with others that are used within their community.